Pengaruh Kredibilitas Youtuber Terhadap Keterlibatan Mahasiswa - Eldhia, Kesya; Fuady, Ikhsan (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2023)
Deddy Corbuzier's YouTube account is growing quite rapidly because of a podcast content that conveys information about the Covid-19 virus. The purpose of this study was to find out how big and important the influence of communicator credibility on student behavior in responding to the Covid-19 virus. The independent variable in this study is the credibility of YouTubers with the dimensions of trust, expertise, and attractiveness. While the dependent variable in this study is student involvement with the dimensions of entertainment, negative emotion related to content, pastime, stimulation, and empowerment. This research is an explanative quantitative type using a survey method. Sampling in this study used non-probability sampling with purposive sampling method. The population used is active students of Communication Studies at Padjadjaran University batch 2020 and 2021 as many as 172 students. The data analysis technique is the analysis of validity, reliability, and linear regression. Based on the results of hypothesis testing using the t-test, youtuber credibility has an influence on student involvement in responding to the Covid-19 pandemic. This is evidenced by the t-count that X (source credibility) shows a significance value of 0.226, which is below 0.005 which means it has a significant influence on student involvement in Deddy Corbuzier's YouTube channel.